The Effect Of Weight and Soaking Of Tuber Cuttings In Cow Urine On Sprouting and Seedling Growth White Yam (Dioscorea alata L.) - Julani Buton; Anthony Walsen; Herman Rehatta (JURNAL BUDIDAYA PERTANIAN, 2022)
Research on the effects of seed weight and soaking of tuber cuttings in cow urine on sprouting and seedling growth white yam (D. alata L.). The research was aimed to obtain the optimal cutting weight and cow urine concentration on the speed of bud growth of the tuber cuttings. The research was carried out in February-April 2018, in the Greenhouse of the Faculty of Agriculture, University of Pattimura, Ambon. The research method used was a Randomized Block Design with a 4x3 factorial experiment with 3 replications so that there were 36 experimental units. The first factor tested was the weight of tuber cuttings, consisting of 4 treatment levels, i.e. 10-15 g, 20-25 g, 30-35 g, 100-105 g. The second factor was the concentration of fresh cow urine, consists of 3 treatment levels, i.e. at concentration of 0%, 15% and 30%. The results showed that the weight of 100-105 g as a control gave the best results on the number of buds, the number of shoots formed, shoot length (cm2), leaf area (cm2), number of leaves, net assimilation rate (g/cm2/week), plant growth rate (g /cm2/week), root length (cm) and number of roots. Cow urine treatment at 30% concentration produced the best seed growth compared to 15% concentration and 0% (without urine treatment). The use of tuber cutting weighing 10-15 g produced seedlings that could develop into productive plants.